Synthesis, characterization, and adsorption properties of magnetic Fe3O4@graphene nanocomposite - Yao, Yunjin.; Miao, S.; Liu, Shi Zhen; Li, Ping; Sun, Hongqi; Wang, Shaobin (Elsevier BV, 2012)
This paper reports the synthesis of magnetic Fe3O4@graphene composite (FGC) and utilization in dye removal from aqueous media. The structural, surface, and magnetic characteristics of the nanosized composite were investigated by field emission scanning electron microscopy, transmission electron microscopy, energy-dispersive X-ray spectrometer, powder X-ray diffraction, Fourier transform infrared, and thermogravimetric analysis. Through a chemical deposition method, Fe3O4 nanoparticles in size of 30 nm were homogeneously dispersed onto graphene sheets. Adsorption isotherm and kinetics of methylene blue (MB) and Congo red (CR) onto FGC were studied in a batch system. The maximum adsorption capacities of MB and CR on FGC were found to be 45.27 and 33.66 mg/g, respectively. The second-order kinetic equation could best describe the sorption kinetics. The findings of the present work highlight the facile fabrication of magnetic FGC and application in adsorption and separation.